PENGARUH PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) DINI DENGAN KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN: Systematic Review - Syamsi Jellena Aisadeawi, (2021)
WHO has set the standard for the incidence of stunting in a country not to be more than 20%. While in 2019, the incidence of stunting is 27.6% in Indonesia. According to WHO, one of the factors that increase the incidence of stunting is the initiation of complementary feeding before 6 months. The aims of this study is to determine whether early complementary feeding affects stunting in children between 6-24 months. This study used a systematic review method. Based on PRISMA-P 2015, Journal searches were conducted on Pubmed and ProQuest with keywords (stunting AND early complementary feeding) and also Google Scholar with keywords (stunting AND early complementary feeding AND 6-24). Journal quality assessment used the JBI Critical Appraisal Checklist. Early complementary feeding has an effect on the incidence of stunting in children aged 6-24 months and children who are given early complementary feeding have a greater risk of stunting than children who are given timely complementary feeding.